Self-esteem and future career orientation among adolescents at the X Orphanage - Thifaalya, Diandra; Purwanti, Margaretha (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
This study aims to examine self-esteem and future career orientation among adolescents at the X Orphanage. Preliminary interviews indicated that the majority of adolescents at the X Orphanage lacked self-esteem and suffered confusions about future career. This study employed a descriptive approach and a mixed method, involving 28 adolescents aged 14-21 years living at the X Orphanage. The adolescents’ self-esteem was measured using the Self-Esteem Inventory with the reliability score of 0.88, while future career orientation was assessed using the Future Career Orientation questionnaire with the reliability score of 0.905. Interviews were conducted to collect more in-depth information about factors influencing self-esteem and career planning. Descriptive statistics and content analysis were adopted to analyze quantitative and qualitative data. The results of this study showed that majority of adolescents at the X Orphanage had moderate to high levels of self-esteem and moderate clarity in future career orientation. Support and fulfilled needs contribute to their positive self-esteem and sufficiently clear future career orientation. However, some adolescents were found to have low self-esteem within the context of social relationships and demonstrate vague career planning. These results highlight the importance of environmental support for orphanage adolescents to foster their self-esteem and enhance career planning.